Paparan Timbal (Pb) Pada (Scylla sp) Pasca Tambang Gunung Botak - Abdollah, Azwar; Sohilauw, Indrayani Sima Sima (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
Mangrove forests are referred to as mangrove forests and are an environment that is often used by the community to be used as fishing locations, this is because there are many fauna in the form crabs, fish, and shrimp. Mangrove forest is an environment close to Bald Mountain which is a gold mining site.that place also occurs gold processing with chemicals that can assist in the gold processing. The lead waste generated from the process of community activities working as gold miners gold mining flows through rivers that cross the mangrove forest, feared that it can disrupt the habitat of plants and animals that live in that environment. It can also be dangerous for local people if they consume food from fishing rods that have been contaminated by lead waste. The type of research used is descriptive qualitative using a laboratory experimental approach to find the lead content (Pb) in (Scylla) obtained from (Scylla) that lives in the Anahoni Mangrove Forest. Sampling is taken at random up three spots (each spot consists 3 points and each point consists of 6 birds). The Pb content of Scylla sp. From results of laboratory tests, it is known that there is heavy metal (Pb) content in (Scylla) living in Anahoni Mangrove Forest, Buru Regency. The average heavy metal content (Pb) in (Scylla). different samples, namely sample I an average of 2,91292 ppm, sample II an average of 2,91292 ppm and sample III an average of 3,73749 ppm. Keywords: Mangrove Crab. Lead, Pb, Serrata, Scilla